(untitled) (BIRDEM Medical Journal, 2020)
Re-infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and co-infection by dengue virus and SARS-CoV-2 are possible. We report a case of dengue haemorrhagic fever, occurring in a young Bangladeshi man, who concurrently tested positive for SARS-CoV-2 infection by reverse transcriptase polymerase chain reaction (RT-PCR). Four months previously, he suffered a mild form of corona virus disease 2019 (COVID-19). This case is reported to make the physicians aware that, co-infections are possible in this COVID-19 pandemic, specially in dengue endemic regions and countries like Bangladesh. Birdem Med J 2020; 10, COVID Supplement: 105-106